Investigating Apology Strategy among Male and Female Kurdish Bilinguals at Ilam. (21st May 2015) - Ghanbari, Halimeh; Jamalinesari, Ali; Gowhary, Habib; Azizifar, Akbar
Abstract: The present study was aimed at exploring and describing apology strategies among Kurdish bilinguals in Ilam, Iran. It attempts to systematize the various strategies used for the purpose of apologizing from the pragmatic point of view. The current study involves 80 subjects of Kurdish bilinguals in Ilam, consisting of 40 male and 40 female subjects. The subjects were chosen randomly to participate in this study. The data of this study was collected through a controlled elicitation method based on a questionnaire which is a modified version of 'Discourse Compilation Test'. Descriptive and inferential statistical such as T-Test have been used to show the meaningfulness of the relationship between gender of respondents and their apology strategies. The prime finding of this study revealed that there is no meaningful relationship between gender and apology strategies used by Ilami people. The results indicated that respondents have frequent tendency toward using "explanation", "taking responsibility" and "offer of repair" strategies. So, they do not have much inclination toward intensification and concern for the hearer.